A temperature-variable thermal conductivity coefficient composite phase change material for lithium ion battery thermal management and thermal runaway blocking

By using a layered structure of composite phase change materials and thermally variable thermal conductivity materials, the problem of thermal runaway propagation in lithium-ion batteries under high-temperature conditions is solved, achieving efficient thermal management and safety protection for lithium battery modules.

CN123040434APending Publication Date: 2026-11-06CHINA UNIV OF MINING & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611074858.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing thermal management materials for lithium-ion batteries cannot effectively block the propagation of thermal runaway under high-temperature conditions, and the traditional thermally conductive-insulating-thermally conductive structure affects the latent heat recovery of phase change materials, resulting in a decline in thermal management capabilities.

Method used

By employing a layered structure of composite phase change materials and temperature-varying thermal conductivity materials, the thermal conductivity of the microcapsule phase change materials and thermally expanding microspheres is reversibly changed at different temperatures. Combined with multi-walled carbon nanotubes and an elastic support framework, multiple temperature buffers and thermal runaway barriers are formed.

Benefits of technology

It maintains good thermal conductivity at normal temperatures and spontaneously reduces thermal conductivity at abnormally high temperatures, thus blocking the propagation of thermal runaway and improving the thermal management and safety of lithium battery modules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
Patent Text Reader

Abstract

This invention belongs to the field of lithium-ion battery material technology and discloses a temperature-varying thermal conductivity composite phase change material for thermal management and thermal runaway prevention in lithium-ion batteries. It includes a composite phase change material layer with enhanced thermal conductivity and flame retardancy, and a temperature-varying thermal conductivity material layer whose overall equivalent thermal conductivity decreases with increasing temperature. This is an integrated composite phase change material with multiple temperature buffering capabilities for both thermal management and thermal runaway prevention. Within the normal operating temperature range of lithium-ion batteries, it maximizes the thermal management advantages of the phase change material and prevents the diffusion of high temperatures within the battery module in situations where battery temperatures are too high or even thermal runaway occurs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery material technology. The invention relates to a composite phase change material with temperature-varying thermal conductivity for thermal management and thermal runaway prevention of lithium-ion batteries. Background Technology

[0002] The new energy vehicle industry is developing rapidly, and new energy power batteries, especially lithium-ion batteries, have been widely used due to their advantages such as high energy density and long cycle life. However, lithium-ion batteries need to operate within a certain temperature range to achieve optimal performance. Furthermore, excessively high temperatures can lead to thermal abuse, causing thermal runaway and potentially resulting in fires or even explosions, seriously threatening people's lives and property.

[0003] Phase change materials (PCMs) are simple in structure and low in cost. They can absorb heat generated by the battery using their latent heat, thereby maintaining the stability of the battery's operating temperature, making them a highly regarded passive thermal management method for battery modules. By adding other components to single-component organic or inorganic PCMs, their flexibility, thermal conductivity, and flame retardancy can be optimized. Thermally enhanced composite PCMs, with their excellent thermal conductivity, can quickly dissipate heat from the battery surface and fully utilize their latent heat for efficient thermal management. However, when the temperature of a single battery cell in the module rises abnormally, the high thermal conductivity of these materials can also accelerate the diffusion of high temperatures to adjacent cells. While combining them with thermal insulation materials to form a "thermal conductive-thermal insulating-thermal conductive" structure can suppress heat transfer between battery cells, it also affects the recovery of the PCM's latent heat, thus impacting its long-term thermal management capabilities. Therefore, developing a temperature-varying thermal conductivity composite PCM that combines the advantages of battery module thermal management and thermal runaway protection is particularly important. Summary of the Invention

[0004] To overcome the shortcomings of existing technologies, this invention provides a composite phase change material with variable thermal conductivity for thermal management and thermal runaway prevention in lithium-ion batteries. This material maximizes the thermal management advantages of the phase change material within the normal operating temperature range of lithium-ion batteries and prevents the diffusion of high temperatures within the battery module in situations where battery temperatures are too high or thermal runaway occurs. It is an integrated composite phase change material with multiple temperature buffering capabilities for both thermal management and thermal runaway prevention.

[0005] The above-mentioned objective of this invention is achieved through the following technical solution: A temperature-varying thermal conductivity composite phase change material for thermal management and thermal runaway prevention of lithium-ion batteries includes a composite phase change material layer with enhanced thermal conductivity and flame retardancy, and a temperature-varying thermal conductivity material layer with an overall equivalent thermal conductivity that decreases with increasing temperature.

[0006] The composite phase change material layer is composed of composite phase change materials, the raw materials of which include, by mass fraction: 6.16%-13.67% expanded graphite, 3.43%-8.35% flame retardant, 10.41%-17.98% support filler, and 60%-80% phase change material.

[0007] The thermal conductivity material layer consists of a functional framework and a filler phase, with a mass percentage of 6.25 wt% to 93.75 wt%. The functional framework comprises, by mass fraction, 73.61% elastic support framework, 25.07% multi-walled carbon nanotubes, 0.97% tannic acid, and 0.35% ferric chloride. The filler phase comprises, by mass fraction, 50%-60% polymer matrix, 10.55%-15.39% expanded graphite, 23.69%-25.78% microencapsulated phase change material, and 5.76%-8.83% thermally expandable microspheres.

[0008] Furthermore, in the composite phase change material, the flame retardant is any one or more of hexaphenoxycyclotriphosphazene, ammonium polyphosphate, and triphenyl phosphate; the support filler is any one or more of epoxy resin, polyurethane, and silicone rubber; and the phase change material is an organic phase change material, specifically any one or more of paraffin wax, polyethylene glycol, and lauric acid.

[0009] Furthermore, in the temperature-varying thermal conductivity material layer, the polymer matrix is ​​any one or more of room-temperature vulcanizing silicone rubber, polyurethane elastomer, and EPDM rubber; the elastic support skeleton is any one or more of melamine sponge, polyimide sponge, and polyurethane sponge. The microcapsule phase change material consists of a flexible polymer as the outer shell and a high-melting-point phase change material as the inner core, with a particle size of 30-50µm, an expansion temperature of 74-77℃, and an expansion ratio of 7-12%. The flexible polymer is polyurethane, and the high-melting-point phase change material is 75# paraffin wax. The thermally expandable microspheres consist of a thermoplastic polymer as the outer shell and a low-boiling-point liquid alkane compound as the inner core, with a particle size of 10-16µm, an initial expansion temperature of 95-102℃, and a maximum expansion temperature of 136-144℃. The thermoplastic polymer is an acrylate copolymer, and the low-boiling-point liquid alkane compound is isobutane, n-pentane, isopentane, or a mixture thereof.

[0010] Furthermore, the multi-walled carbon nanotubes have a diameter of 8-15 nm, a length of 3-12 μm, and a specific surface area >233 m². 2 / g of multi-walled carbon nanotubes.

[0011] Preferably, in the composite phase change material, the expanded graphite is prepared by treating expandable graphite with an expansion rate ≥200mL / g and an initial particle size of 80 mesh at 800℃ for 1min; the flame retardant is hexaphenoxycyclotriphosphazene with an average particle size ≤10µm and a decomposition temperature ≥250℃; the supporting filler is bisphenol A type epoxy resin and its curing agent (the curing agent is a commercially available product and is not specifically limited), with an initial viscosity of 40000~45000mPa·s; the phase change material is polyethylene glycol with a number average molecular weight of 1500, a phase change temperature of 43-46℃, and a latent heat value ≥160J / g.

[0012] Preferably, in the temperature-dependent thermal conductivity material layer, the expanded graphite is 1000-mesh expanded graphite powder; the polymer matrix is ​​addition-type two-component room temperature vulcanizing silicone rubber and its curing agent (the curing agent is a commercially available product and is not specifically limited), with an initial viscosity of 5,000~20,000 mPa·s and a Shore A hardness of 15~30 after curing; the elastic support skeleton is melamine sponge with a porosity >95%.

[0013] Furthermore, the present invention also claims protection for the preparation method of the temperature-varying thermal conductivity composite phase change material for thermal management and thermal runaway prevention of lithium-ion batteries, wherein the composite phase change material layer is prepared by raw material drying, melt blending, crosslinking pre-curing and hot pressing shaping process; and the temperature-varying thermal conductivity material layer is prepared by modified dip coating, dispersion curing, vacuum impregnation and volatilization shaping process.

[0014] This invention also seeks protection for the application of the temperature-varying thermal conductivity composite phase change material for thermal management and thermal runaway prevention of lithium-ion batteries prepared by the above-described method in lithium battery modules.

[0015] In practical applications, the composite phase change material layer, thermal conductivity material layer, and composite phase change material layer are stacked in a 1:1:1 ratio, and aluminum foil is used for overall encapsulation.

[0016] The advantages of this invention compared to the prior art are: This invention provides a temperature-varying thermal conductivity composite phase change material for thermal management and thermal runaway prevention in lithium-ion batteries, achieving efficient thermal management. Through a sandwich structure of "composite phase change material - temperature-varying thermal conductivity material - composite phase change material," this invention achieves multiple temperature buffering effects between battery cells. While maintaining excellent thermal conductivity between battery cells under normal temperature conditions, it can spontaneously and reversibly enhance thermal insulation performance at abnormally high temperatures, simultaneously blocking the propagation of thermal runaway. This invention helps optimize the thermal management capabilities of lithium battery modules, slows the spread of high temperatures, and even blocks the propagation of thermal runaway, thereby improving the safety level of battery modules.

[0017] This invention utilizes temperature-varying thermal conductivity materials to assist in the thermal management function of the composite phase change material and to protect against thermal runaway in lithium battery packs. Conventional thermal switching materials typically utilize high-temperature deformation of the material to trigger cooling device circuits, or physically and irreversibly disrupt the internal heat conduction paths of the material to achieve a sudden change in thermal conductivity. This invention introduces microcapsule phase change materials and thermally expandable microspheres, which are uniformly dispersed in a silicone rubber matrix. The phase change expansion of the microcapsule phase change material core at 74-77℃ causes the flexible outer shell to expand, opening up the surrounding silicone rubber matrix and disrupting the contact network of expanded graphite and multi-walled carbon nanotubes. Thanks to the excellent resilience of the silicone rubber matrix and melamine sponge, the thermal conductivity is restored as the temperature drops and the microcapsules shrink. Meanwhile, the low-boiling-point liquid alkane core of the thermally expandable microspheres boils and vaporizes at 95-102℃, causing the thermoplastic polymer outer shell to expand violently, compressing the elastic skeleton, disrupting the thermal conductivity network, and leaving air gaps, resulting in a sharp drop in thermal conductivity. Furthermore, the microcapsule phase change material itself possesses a certain latent heat, providing a buffering effect against the diffusion of abnormally high temperatures.

[0018] The material provided by this invention, within the normal temperature range, exhibits good thermal conductivity due to its temperature-varying thermal conductivity coefficient. This alleviates the problem in traditional "thermal conduction-insulation-thermal conduction" structures where the heat of the thermally conductive phase change material cannot be dissipated in a timely manner, thus affecting its latent heat recovery. Furthermore, under abnormal high temperature and fire conditions, the high thermal insulation performance of the temperature-varying thermal conductivity coefficient material effectively blocks the propagation of thermal runaway. Therefore, this invention achieves efficient thermal management and dual-buffered thermal runaway protection for lithium battery packs. Attached Figure Description

[0019] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.

[0020] Figure 1 This is a schematic diagram showing the location of the temperature-varying thermal conductivity composite phase change material used for thermal management and thermal runaway prevention of lithium-ion batteries in the battery module.

[0021] Figure 2 This is a schematic diagram of the working material of the temperature-varying thermal conductivity composite phase change material used in the thermal management and thermal runaway prevention of lithium-ion batteries according to the present invention.

[0022] In the figure: 1. Temperature-dependent thermal conductivity composite phase change material; 2. Composite phase change material layer; 3. Temperature-dependent thermal conductivity material layer; 4. Aluminum foil. Detailed Implementation

[0023] The present invention is described in detail below through specific embodiments, but this does not limit the scope of protection of the present invention. Unless otherwise specified, the experimental methods used in the present invention are all conventional methods, and the experimental equipment, materials, reagents, etc. used can all be obtained commercially.

[0024] Example 1 A temperature-varying thermal conductivity composite phase change material for thermal management and thermal runaway prevention of lithium-ion batteries includes a composite phase change material layer with enhanced thermal conductivity and flame retardancy, and a temperature-varying thermal conductivity material layer with an overall equivalent thermal conductivity that decreases with increasing temperature.

[0025] The composite phase change material layer is composed of composite phase change materials, the raw materials of which include, by mass fraction: 13.67% expanded graphite, 8.35% flame retardant, 17.98% support filler, and 60% phase change material.

[0026] The thermal conductivity material layer consists of a functional framework and a filler phase, with a mass percentage ratio of 6.25 wt% to 93.75 wt%. The functional framework comprises, by mass fraction, 73.61% elastic support framework, 25.07% multi-walled carbon nanotubes, 0.97% tannic acid, and 0.35% ferric chloride. The filler phase comprises, by mass fraction, 50% polymer matrix, 15.39% expanded graphite, 25.78% microencapsulated phase change material, and 8.83% thermally expandable microspheres. The tannic acid solution is prepared as follows: 0.2 wt% tannic acid, 99.8 wt% deionized water; the ferric chloride solution is prepared as follows: 0.2 wt% ferric chloride, 99.8 wt% deionized water; and the multi-walled carbon nanotube solution is prepared as follows: 0.5 wt% multi-walled carbon nanotubes, 99.5 wt% deionized water. In the composite phase change material, the flame retardant is hexaphenoxycyclotriphosphazene with an average particle size ≤10µm and a decomposition temperature ≥250℃; the expanded graphite is prepared by treating expandable graphite with an expansion rate ≥200mL / g and an initial particle size of 80 mesh at 800℃ for 1min; the supporting filler is bisphenol A type epoxy resin and its curing agent (the curing agent is a commercially available product and is not specifically limited here), with an initial viscosity of 40000~45000mPa·s; the phase change material is polyethylene glycol with a number average molecular weight of 1500, a phase change temperature of 43-46℃, and a latent heat value ≥160J / g.

[0027] Furthermore, in the temperature-varying thermal conductivity material layer, the functional framework is derived from an elastic support framework modified with tannic acid-ferric chloride and then coated with multi-walled carbon nanotubes; the elastic support framework is melamine sponge with a porosity >95%, and the polymer matrix is ​​addition-type two-component room temperature vulcanizing silicone rubber and its curing agent (the curing agent is a commercially available product and is not specifically limited), with an initial viscosity of 5,000~20,000 mPa·s and a Shore A hardness of 15~30 after curing; the multi-walled carbon nanotubes have an outer diameter of 8-15 nm, a length of 3-12 µm, and a specific surface area >233 m². 2 / g; Expanded graphite is 1000 mesh expanded graphite powder; Microcapsule phase change material is composed of a flexible polymer as the outer shell and a high-melting-point phase change material as the inner core, with a particle size of 30-50µm, an expansion temperature of 74-77℃, and an expansion ratio of 7-12%. The flexible polymer is polyurethane, and the high-melting-point phase change material is 75# paraffin wax; Thermally expandable microspheres are composed of a thermoplastic polymer as the outer shell and a low-boiling-point liquid alkane compound as the inner core, with a particle size of 10-16µm, an initial expansion temperature of 95-102℃, and a maximum expansion temperature of 136-144℃. The thermoplastic polymer is an acrylate copolymer, and the low-boiling-point liquid alkane compound is isobutane, n-pentane, isopentane, or a mixture thereof.

[0028] The preparation method specifically includes the following steps: S1. Raw material drying Accurately weigh the expanded graphite and hexaphenoxycyclotriphosphazene according to the raw material ratio and place them in a vacuum drying oven at 60°C for more than 12 hours to completely remove the surface adsorbed moisture and prevent the generation of bubbles during subsequent hot pressing and shaping processes.

[0029] S2, melt blending Accurately weigh polyethylene glycol according to the raw material ratio and place it in a beaker. Heat it in an oil bath at 65°C until it is completely melted and becomes a transparent liquid. Turn on the mechanical stirrer at 600 rpm and slowly add the dried hexaphenoxycyclotriphosphazene from S1 in batches. Continue stirring for 15 minutes until it is evenly dispersed. Continue to slowly add the dried expanded graphite from S1 in batches and continue stirring at a constant temperature for 30 minutes to obtain a uniform black viscous initial blend.

[0030] S3, Crosslinking Pre-curing Accurately weigh the epoxy resin and its curing agent according to the raw material ratio, mix them evenly, and add them to the initial blend obtained in S2. Increase the speed to 1000 rpm and continue stirring at a constant temperature for 5 minutes to obtain a uniform viscous mixture.

[0031] S4, Hot pressing and shaping The viscous mixture in S3 is quickly transferred to a stainless steel mold pre-coated with silicone oil release agent, and the surface is smoothed. The mold is then moved into a hot press preheated to 80°C, the mold is closed, and a vertical pressure of 5 MPa is applied. This temperature and pressure are maintained for 3 hours. The hot press is then turned off, and the pressure is maintained until the mold cools naturally to room temperature. The pressure is then released, the mold is opened, and the composite phase change material is removed to obtain the composite phase change material layer.

[0032] S5, Modified Dip Coating Melamine sponges were ultrasonically cleaned in anhydrous ethanol for 10 minutes to remove debris and surface impurities, and then dried in a 60℃ oven for 2 hours. Multi-walled carbon nanotubes, tannic acid, and ferric chloride were precisely weighed according to the raw material ratio and placed into three beakers, along with the corresponding proportions of deionized water. The mixtures were stirred at room temperature for 12 hours to obtain homogeneous tannic acid and ferric chloride solutions. These solutions were then ultrasonically treated in a 400W ice-water bath at room temperature for 2 hours to obtain a stable and homogeneous multi-walled carbon nanotube solution. The dried melamine sponges were then immersed in the tannic acid solution for 1 hour, and excess liquid was gently squeezed out. Next, the melamine sponges soaked in the tannic acid solution were quickly transferred to a ferric chloride solution and immersed for 20 minutes to induce a coordination cross-linking reaction on the surface, forming… A dense, bluish-black coating is applied. The melamine sponge, after being soaked in a tannic acid and ferric chloride solution, is rinsed with deionized water until the washing solution is colorless. It is then placed in a 60°C forced-air drying oven for 2 hours until completely dry. The melamine sponge with the tannic acid-ferric chloride coating is immersed in a multi-walled carbon nanotube solution and slowly squeezed five times below the liquid surface. Relying on the coating's strong hydrophilicity and adhesion, the multi-walled carbon nanotubes are firmly anchored to the surface of the sponge's deep pores. The melamine sponge with the adsorbed multi-walled carbon nanotubes is removed from the solution, and the surface droplets are gently blotted dry with dry filter paper. It is then immediately placed in a -80°C ultra-low temperature freezer for rapid freezing, and finally transferred to a freeze dryer for 24 hours to allow the ice crystals to sublimate directly, resulting in a black, highly elastic functional skeleton with intact internal channels and no deformation.

[0033] S6, Dispersion Curing Accurately weigh room temperature vulcanizing silicone rubber and its curing agent (components A and B) according to the raw material ratio. Add room temperature vulcanizing silicone rubber (component A) and an equal volume of n-hexane to a beaker. Mix them evenly for 10 minutes using a top-mounted mechanical stirrer at 25°C and 500 rpm to obtain a low-viscosity silicone rubber premix. Accurately weigh expanded graphite, microcapsule phase change material and thermally expanded microspheres according to the raw material ratio. Add them slowly to the silicone rubber premix in sequence while maintaining the temperature and continue stirring for 30 minutes. Add room temperature vulcanizing silicone rubber curing agent (component B) and stir for 5 minutes until completely homogeneous to obtain a mixed filling slurry.

[0034] S7, Vacuum Impregnation Place the high-elasticity functional skeleton prepared by S5 flat into the polytetrafluoroethylene non-stick mold; pour the mixed filling phase slurry prepared by S6 evenly over the high-elasticity thermally conductive skeleton in the mold, so that it naturally covers the skeleton; place the mold in a vacuum drying oven, close the valve, evacuate to -0.09MPa, maintain for 3 minutes, then slowly open the vent valve to restore to normal pressure, and continue to maintain for 3 minutes; repeat the above cycle of "vacuuming-pressure holding-venting and restoration" 3 times until the slurry surface is level and no more bubbles emerge from the inside of the sponge when evacuating.

[0035] S8, Volatilization and Setting Transfer the mold after impregnation in S7 to a fume hood and let it stand at room temperature for 12 hours. Then place it in a vacuum drying oven at 40°C for 6 hours to ensure that the hexane solvent inside has completely evaporated. After the solvent has evaporated, transfer the mold to a constant temperature oven at 50°C and continue to cure for 24 hours. Then turn off the heating and let the mold cool to room temperature before opening the mold and taking out the thermal conductivity material layer.

[0036] The composite phase change material layer prepared in Example 1 has a thermal conductivity of 3.22 W·m. -1 ·K -1 The thermal conductivity of the material layer at room temperature is 1.59 W·m. -1 ·K -1 At 80℃, the thermal conductivity drops to 1.03 W·m. -1 ·K -1 (The thermal conductivity recovered to 1.58 W·m after the temperature dropped back to room temperature) -1 ·K -1 ), and further decreased to 0.05 W·m at 100℃. -1 ·K -1 .

[0037] Example 2 The composite phase change material layer is composed of composite phase change materials, the raw materials of which include, by mass fraction: 10.36% expanded graphite, 4.61% flame retardant, 15.03% support filler, and 70% phase change material.

[0038] The thermal conductivity material layer consists of a functional framework and a filler phase, with a mass percentage of 6.25 wt% to 93.75 wt%. The functional framework comprises, by mass fraction, 73.61% elastic support framework, 25.07% multi-walled carbon nanotubes, 0.97% tannic acid, and 0.35% ferric chloride. The filler phase comprises, by mass fraction, 55% polymer matrix, 13.24% expanded graphite, 24.15% microcapsule phase change material, and 7.61% thermally expandable microspheres.

[0039] Everything else is the same as in Example 1. In Example 2, the thermal conductivity of the composite phase change material layer was 2.47 W·m. -1 ·K -1 The thermal conductivity of the material layer at room temperature is 1.24 W·m. -1 ·K -1 At 80℃, the thermal conductivity drops to 0.88 W·m. -1 ·K -1 (The thermal conductivity recovered to 1.24 W·m after the temperature dropped back to room temperature) -1 ·K -1), and further decreased to 0.06 W·m at 100℃. -1 ·K -1 .

[0040] Example 3 The composite phase change material layer is composed of composite phase change materials, the raw materials of which include, by mass fraction: 6.16% expanded graphite, 3.43% flame retardant, 10.41% support filler, and 80% phase change material.

[0041] The thermal conductivity material layer consists of a functional framework and a filler phase, with a mass percentage of 6.25 wt% to 93.75 wt%. The functional framework comprises, by mass fraction, 73.61% elastic support framework, 25.07% multi-walled carbon nanotubes, 0.97% tannic acid, and 0.35% ferric chloride. The filler phase comprises, by mass fraction, 60% polymer matrix, 10.55% expanded graphite, 23.69% microcapsule phase change material, and 5.76% thermally expandable microspheres.

[0042] Everything else is the same as in Example 1. In Example 3, the thermal conductivity of the composite phase change material layer was 1.96 W·m. -1 ·K -1 The thermal conductivity of the material layer at room temperature is 0.97 W·m. -1 ·K -1 At 80℃, the thermal conductivity drops to 0.65 W·m. -1 ·K -1 (The thermal conductivity recovered to 0.96 W·m after the temperature dropped back to room temperature) -1 ·K -1 ), and further decreased to 0.08 W·m at 100℃. -1 ·K -1 .

[0043] Application Example 1 The composite phase change material layer and the temperature-varying thermal conductivity material layer prepared in Example 1 were stacked in a 1:1:1 ratio in the order of "composite phase change material layer - temperature-varying thermal conductivity material layer - composite phase change material layer". Aluminum foil of corresponding sizes was cut, and the entire assembly was sealed using a heat-sealing machine. This yielded a temperature-varying thermal conductivity composite phase change material for lithium-ion battery thermal management and thermal runaway prevention. Testing showed that the overall equivalent thermal conductivity at room temperature, 80°C, and 100°C was 2.40 W·m. -1 ·K -1 1.88 W·m -1 ·K -1 With 0.15 W·m -1 ·K -1The prepared temperature-varying thermal conductivity composite phase change material structure exhibits good thermal conductivity and heat storage performance under normal temperature conditions, and its overall thermal conductivity decreases significantly under high temperature conditions, demonstrating a good thermal runaway prevention effect.

[0044] Application Example 2 The composite phase change material layer and the temperature-varying thermal conductivity material layer prepared in Example 2 were stacked in a 1:1:1 ratio in the order of "composite phase change material layer - temperature-varying thermal conductivity material layer - composite phase change material layer". Aluminum foil of corresponding sizes was cut, and the entire assembly was sealed using a heat-sealing machine. This yielded a temperature-varying thermal conductivity composite phase change material for lithium-ion battery thermal management and thermal runaway prevention. Testing showed that the overall equivalent thermal conductivity at room temperature, 80°C, and 100°C was 1.86 W·m. -1 ·K -1 1.54 W·m -1 ·K -1 With 0.17 W·m -1 ·K -1 The prepared temperature-varying thermal conductivity composite phase change material structure exhibits good thermal conductivity and heat storage performance under normal temperature conditions, and its overall thermal conductivity decreases significantly under high temperature conditions, demonstrating a good thermal runaway prevention effect.

[0045] Application Example 3 The composite phase change material layer and the temperature-varying thermal conductivity material layer prepared in Example 3 were stacked in a 1:1:1 ratio in the order of "composite phase change material layer - temperature-varying thermal conductivity material layer - composite phase change material layer". Aluminum foil of corresponding sizes was cut, and the entire assembly was sealed using a heat-sealing machine. This yielded a temperature-varying thermal conductivity composite phase change material for lithium-ion battery thermal management and thermal runaway prevention. Testing showed that the overall equivalent thermal conductivity at room temperature, 80°C, and 100°C was 1.46 W·m. -1 ·K -1 1.17 W·m -1 ·K -1 With 0.22 W·m -1 ·K -1 The prepared temperature-varying thermal conductivity composite phase change material structure exhibits good thermal conductivity and heat storage performance under normal temperature conditions, and its overall thermal conductivity decreases significantly under high temperature conditions, demonstrating a good thermal runaway prevention effect.

[0046] As can be seen from Examples 1-3, the temperature-varying thermal conductivity composite phase change material of the present invention for thermal management and thermal runaway protection of lithium battery packs achieves multiple temperature buffering effects when temperature needs to propagate from one battery cell to an adjacent battery cell, passing through the composite phase change material layer, the temperature-varying thermal conductivity layer, and the composite phase change material layer in sequence. Within the normal operating temperature range of lithium batteries (typically below 60°C), after the phase change material absorbs heat and undergoes a phase change, the temperature-varying thermal conductivity interlayer still possesses good thermal conductivity, which helps in the recovery of the latent heat of the composite phase change material. This ensures the effectiveness of composite phase change materials in long-term thermal management. When the battery heats up abnormally but does not cause thermal runaway (below 90°C), the thermal conductivity of the temperature-changing thermal conductivity material undergoes a reversible change, slowing down the diffusion of high temperature within the battery pack and thus improving the regulation capability of the battery thermal management system. When the battery temperature exceeds the critical value (above 90°C), the battery separator will decompose, which can easily cause a chemical chain reaction inside the battery, ultimately leading to irreversible thermal runaway. At this time, the temperature-changing thermal conductivity material will also drop sharply, thus preventing the spread of thermal runaway.

[0047] The embodiments described above are merely preferred embodiments of the present invention, and not all feasible embodiments of the present invention. Any obvious modifications made by those skilled in the art without departing from the principles and spirit of the present invention should be considered to be included within the scope of protection of the claims of the present invention.

Claims

1. A temperature-dependent thermal conductivity coefficient composite phase change material for lithium-ion battery thermal management and thermal runaway mitigation, characterized in that, It includes a composite phase change material layer with enhanced thermal conductivity and flame retardancy, and a temperature-varying thermal conductivity material layer with an overall equivalent thermal conductivity that decreases with increasing temperature.

2. The temperature-dependent thermal conductivity composite phase change material for thermal management and thermal runaway mitigation of lithium-ion batteries of claim 1, wherein, The composite phase change material layer is composed of composite phase change materials, the raw materials of which include, by mass fraction: 6.16%-13.67% expanded graphite, 3.43%-8.35% flame retardant, 10.41%-17.98% support filler, and 60%-80% phase change material.

3. The temperature-varying thermal conductivity composite phase change material for thermal management and thermal runaway prevention of lithium-ion batteries as described in claim 1, characterized in that, The temperature-varying thermal conductivity material layer consists of a functional skeleton and a filler phase, with the mass percentages of the functional skeleton and the filler phase being 6.25 wt% and 93.75 wt%, respectively.

4. The temperature-varying thermal conductivity composite phase change material for thermal management and thermal runaway prevention of lithium-ion batteries as described in claim 2, characterized in that, The flame retardant is any one or more of hexaphenoxycyclotriphosphazene, ammonium polyphosphate, and triphenyl phosphate; the support filler is any one or more of epoxy resin, polyurethane, and silicone rubber; the phase change material is an organic phase change material, specifically any one or more of paraffin wax, polyethylene glycol, and lauric acid.

5. The temperature-varying thermal conductivity composite phase change material for thermal management and thermal runaway prevention of lithium-ion batteries as described in claim 3, characterized in that, The functional framework is made of the following raw materials: by mass fraction, 73.61% elastic support framework, 25.07% multi-walled carbon nanotubes, 0.97% tannic acid and 0.35% ferric chloride.

6. The temperature-varying thermal conductivity composite phase change material for thermal management and thermal runaway prevention of lithium-ion batteries as described in claim 3, characterized in that, The filler phase consists of the following raw materials by mass fraction: 50%-60% polymer matrix, 10.55%-15.39% expanded graphite, 23.69%-25.78% microcapsule phase change material, and 5.76%-8.83% thermally expandable microspheres.

7. The temperature-varying thermal conductivity composite phase change material for thermal management and thermal runaway prevention of lithium-ion batteries as described in claim 3, characterized in that, In the temperature-dependent thermal conductivity material layer, the polymer matrix is ​​any one or more of room temperature vulcanizing silicone rubber, polyurethane elastomer, and EPDM rubber; the elastic support skeleton is any one or more of melamine sponge, polyimide sponge, and polyurethane sponge.

8. The temperature-varying thermal conductivity composite phase change material for thermal management and thermal runaway prevention of lithium-ion batteries as described in claim 3, characterized in that, The microcapsule phase change material consists of a flexible polymer as the outer shell and a high-melting-point phase change material as the inner core. The particle size is 30-50µm, the expansion temperature is 74-77℃, and the expansion ratio is 7-12%. The flexible polymer is polyurethane, and the high-melting-point phase change material is 75# paraffin wax.

9. A composite phase change material with variable thermal conductivity for thermal management and thermal runaway prevention in lithium-ion batteries as described in claim 3, characterized in that, The thermally expandable microspheres consist of a thermoplastic polymer shell and a low-boiling-point liquid alkane compound as the inner core. The particle size is 10-16µm, the initial expansion temperature is 95-102℃, and the maximum expansion temperature is 136-144℃. The thermoplastic polymer is an acrylate copolymer, and the low-boiling-point liquid alkane compound is isobutane, n-pentane, isopentane, or a mixture thereof.

10. The application of the temperature-varying thermal conductivity composite phase change material for thermal management and thermal runaway prevention of lithium-ion batteries as described in any one of claims 1-9 in lithium battery modules, characterized in that, The composite phase change material layer, the thermal conductivity material layer, and the composite phase change material layer are stacked in a 1:1:1 ratio and then encapsulated using aluminum foil.